2019
DOI: 10.1093/infdis/jiz392
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Zika Virus Microcephaly in Newborns With the rs3775291 Variant in Toll-Like Receptor 3 and rs1799964 Variant at Tumor Necrosis Factor-α Gene

Abstract: Congenital Zika syndrome (CZS) is a cluster of malformation, and the mechanisms that lead it are still unclear. Using hypothesis-driven candidate genes and their function in viral infections, single-nucleotide polymorphisms (SNPs) were genotyped by quantitative polymerase chain reaction in a sample population from Sergipe State, Brazil. This study shows that rs3775291 SNP at Toll-like receptor 3, which triggers type I interferon antiviral responses in mothers infected by Zika virus during pregnancy, is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 12 publications
2
32
1
2
Order By: Relevance
“…Mild or moderate microcephaly was defined if the head circumference was between 2 and 3 standard deviation (SD) below the mean for sex and age, and severe if it was 3 or more SD below the mean [19]. Children with 2SD of microcephaly were compared to children with 3SD of microcephaly for the frequency of two variables already reported in the literature as related to these phenotypes-trimester of ZIKV infection and TNF gene [20,21]. The results of such analysis are presented in Table 5.…”
Section: Genetic Susceptibility To Czs and Severe Microcephalymentioning
confidence: 99%
“…Mild or moderate microcephaly was defined if the head circumference was between 2 and 3 standard deviation (SD) below the mean for sex and age, and severe if it was 3 or more SD below the mean [19]. Children with 2SD of microcephaly were compared to children with 3SD of microcephaly for the frequency of two variables already reported in the literature as related to these phenotypes-trimester of ZIKV infection and TNF gene [20,21]. The results of such analysis are presented in Table 5.…”
Section: Genetic Susceptibility To Czs and Severe Microcephalymentioning
confidence: 99%
“…Comparable to the identification of the TLR2 2258 G>A SNP, the T allele in SNP rs3775291 of the TLR3 gene is associated with a risk of CZS [86]. Furthermore, a link between the T allele in SNP rs1799964 at tumor necrosis factor α and the severity of ZIKV-induced microcephaly was identified [86].…”
Section: The Advent Of Induced Pluripotent Stem Cells and The Associamentioning
confidence: 96%
“…A case-control study of a Brazilian cohort identified a statistically significant association of maternal adenylate cyclase genes with the development of CZS [85]. Comparable to the identification of the TLR2 2258 G>A SNP, the T allele in SNP rs3775291 of the TLR3 gene is associated with a risk of CZS [86]. Furthermore, a link between the T allele in SNP rs1799964 at tumor necrosis factor α and the severity of ZIKV-induced microcephaly was identified [86].…”
Section: The Advent Of Induced Pluripotent Stem Cells and The Associamentioning
confidence: 99%
See 1 more Smart Citation
“…The human subpopulations most vulnerable to influenza virus infections are children, pregnant women, and persons over 65 years old. [77,190,[193][194][195][196] Human (in vivo) Pathogenic Higher levels of IFN-β in severe vs. nonsevere dengue children [197] Human (in vivo) Pathogenic Higher levels of IFN-β in primary DHF patients compared to those with primary DF [198] ZIKV Human (in vivo) Protective SNP at TLR-3 that decreased IFN-I response has been associated with microcephaly in newborns [232] Human (in vitro) Protective [45][46][47]. Once activated, RIG-I and MDA5 interact with the mitochondrial antiviral-signaling protein (MAVS), leading the activation of NF-κB and IRF-3 to stimulate IFN production (Figure 2).…”
Section: Human Ifn-i Responses To Viral Pathogensmentioning
confidence: 99%